Riscos ambientais e de acidentes de trabalho na ala de pediatria de um hospital universitário: estudo de caso e subsídios para um programa de gestão de riscos - Pimentel, Renan Jamary Guimarães (2024)
The work environment in healthcare institutions is recognized as a high-risk space for accidents and occupational diseases due to the nature and organization of activities in this context. Especially in hospital settings, workers face significant occupational risks in the field of health and safety, where regulations set by the Ministry of Labor and Employment in Brazil are followed. In 2019, a revision of this regulatory system took place, including the Risk Management Program (RMP), which became mandatory for all organizations. The Lauro Wanderley University Hospital (HULW) is required to develop the RMP for all sectors of the institution. Based on these considerations, the central question of this dissertation is: What are the main environmental and accident risks in the pediatric wards of HULW, and how would an RMP address these risks? Thus, the general objective of this dissertation was to propose an RMP with support for HULW, based on an assessment of environmental and occupational risks in the pediatric wards of HULW. The research, conducted as a case study, included occupational safety inspection, risk mapping, and preliminary risk analysis, focusing on activities assigned to pediatricians, nurses, and nursing technicians, who are day shift and on-call staff in the sector. Among the main findings, the identification of biological risk as the most relevant (high) was highlighted, which can occur frequently due to accidents involving sharp objects. Among other environmental risks, no chemical or physical risks were identified in the sector. Safety measures were identified, but gaps were observed in this process during the sector's technical inspection. It is concluded that there are gaps that could compromise the safety of healthcare professionals and that require improvements to ensure protection against biological risks and accidents. Based on this environmental risk mapping, an RMP was developed, which could serve as a foundation to support the overall hospital program.